42PGenome wide copy number analysis of circulating tumour cells in breast cancer liver metastasis. (24th November 2019) - Imani, S; Linglin, Z; Maghsoudloo, M; Wen, Q
Abstract: Background: Circulating tumor cells (CTCs) enter peripheral blood from primary breast cancer tumors and seed liver metastasis (BCLM). The genome-wide sequencing of CTCs offers noninvasive diagnostic factor for survival in BCLM patients, which but has been impeded by low single-cell genome coverage of scarce CTCs. Methods: We conducted a prospective clinical investigation to confirm the diagnostic value of genome-wide sequencing in BCLM. We have developed the genome-wide pattern differences in copy number variations (CNVs) and to improve a CNV signature as an adjunct test for the routine histopathologic classification of BCLM. We compared the consistency and efficiency of genome-wide sequencing of CTCs with other comment detection methods. Furthermore, functional prediction of candidate gene biomarkers was confirmed in BCLM patients. Results: CTCs were isolated from 26 patients with BCLM, 12 of which were successfully profiled for high CTCs (> 15), including matched archival primary tumor from 17 patients. Our results characteristic cancer-metastatic variations and insertions/deletions in exomes of CTCs. Comparison with primary breast tumors in metastatic niches cell revealed similar frequencies of BCLM genomic copy number aberrations. Higher CTCs frequencies (> 35) are correlated with disease severity and metastatic progress, which suggesting effective value of CTCs for variety of staging of BCLM. The CNV pattern of CTC is similar to that of hepatic metastasis, but the mutation pattern of CTC is different from that of primary lesion. Twenty- five genes were identified as a CNV signature of BCLM. Functional pathways analysis shows all these genes might play similar and critical roles in migration and progression of BCLM that could be independent risk factors for BCLM (p < 0.05). Conclusions: Our approach utilized to explore reproducibility of cancer-specific CNVs involved in progression of metastatic breast cancer. Our study contributed a new potential non-invasive biomarker for CTC-based cancer diagnostics of BCLM to monitor therapeutic efficacy of targeted therapies. Editorial acknowledgement: The authorswould like to express their appreciation to appreciate Southwest Medical Universityfor its financial support. We also wish to thank the oncology and pathology technicians of The Affiliated Hospital of Southwest Medical University for their assistance in the work reported here. We also thank the anonymous referee for his/her very helpful comments, which remarkably improved the quality of this research. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.